Pengaruh Atribut-Atribut Kualitas Audit Terhadap Kepuasan Klien - fadhlurokhman, fadhlurokhman; Nurdhiana, Nurdhiana (STIE Widya Manggala, 2009)
The purpose of the research is to find out the influence of experience in auditing, comprehend clients’ industry, responsive to client’s need, obey to general standard, and KAP leaders’ involvement toward clients’ satisfaction at manufacture companies in Semarang. Whereas, the sample of this research is 31 financial managers or controllers at big manufacture company in Semarang. The statistical analysis in this research is multiple linear regression. There are four results of partial hypothesis test. First, it shows that experience in auditing has positive significant influence toward clients’ satisfaction. Second, the hypothesis test of comprehend clients’ industry indicates positive significant influence toward clients’ satisfaction. Third, the test hypothesis of responsive to clients’ need has significant influence toward clients’ satisfaction. Then, the test of obeying to general standard shows positive significant influence toward clients’ satisfaction. The test of KAP leaders’ involvement also shows positive significant influence toward clients’ satisfaction. The result of simultaneous hypothesis test indicates that there is significant influence of experience in auditing, comprehend clients’ industry, responsive to client’s need, obey to general standard, and KAP leaders’ involvement toward clients’ satisfaction.